The platformisation of party politics? - Kate Dommett; Fenwick McKelvey; Glenn Kefford (Journal of Quantitative Description: Digital Media)
Political parties have gone digital. Political scientists in countries around the world have diagnosed the rise of the digital party and traced parties’ adoption of digital technology. Existing attempts to understand parties’ digital practices have focused on the adoption of different tools, with scholars empirically studying and theorizing how and why digital technology is used. What has received less attention is the technical architecture and origins of these tools, questions that have been more directly examined by political communication scholarship. In this paper we entwine insights from these two disciplines, interrogating the idea of ‘platformization’ in the context of political technology. Presenting a unique, longitudinal dataset that captures the technological development of political party websites in 66 parties in 16 countries, we provide unprecedented insight into the evolution of party websites and show evidence of increasing platform dependency. Our findings have important implications for our understanding of parties’ relationship with technology, showing how technological developments and monopolies can lead to increasingly homogenized practice internationally.